Basic mathematics for biochemists / Athel Cornish-Bowden. - Cornish-Bowden, Athel, 1943- (Oxford University Press, 1999)
This volume sets out all the mathematics needed for an undergraduate course in biochemistry, assuming a minimum of prior knowledge. Emphasis is placed on topics necessary for biochemists and all the examples are relevant to biochemistry.